Thinking Mathematically (6th Edition)

Published by Pearson
ISBN 10: 0321867327
ISBN 13: 978-0-32186-732-2

Chapter 6 - Algebra: Equations and Inequalities - 6.1 Algebraic Expressions and Formulas - Exercise Set 6.1: 31

Answer

-33

Work Step by Step

Given -$x^{2}$ -4xy +3$y^{3}$, x=-1, y=-2 Step 1: Put the value of x=-1 and y=-2 for each x and y in the expression =-$(-1)^{2}$ -4(-1)(-2) +3$(-2)^{3}$ Step 2: Evaluate the exponential expression$(-1)^{2}$ = (-1)(-1) = 1 $(-2)^{3}$ = (-2)(-2)(-2) = -8 =-1-4(-1)(-2)+3(-8) Step 3: Multiply 4(-1)(-2) = 8, 3(-8) = -24 = -1-8-24 Step 4: Add and Subtract from left to right first add -1-8 -9-24 = -33
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.